Boosting county economic resilience through digital villages: The dual role of innovation capacity and fiscal investment - Cao, Yang; Teng, Fei (Transformations In Business & Economics, 2026)
Amid rising global economic volatility and the advancing rural revitalization strategy, strengthening the resilience of county economies has become a key prerequisite for safeguarding overall national economic stability. Although previous studies have explored various determinants of economic resilience, empirical evidence remains insufficient with regard to the role and mechanisms of government-led digital policy interventions. To assess whether institutional digitalization serves as a channel through which digital village initiatives shape county-level resilience, this study utilizes the National Digital Village Pilot Program as an exogenous policy shock. Drawing on regional economic resilience theory and technology-biased innovation frameworks, we assemble county-level panel data that cover 2006–2023 and implement a difference-in-differences identification strategy to evaluate the policy’s causal impact. Empirical evidence demonstrates that digital village programs generate significant and robust gains in county economic resilience, and these improvements are primarily driven by two underlying mechanisms: by improving county innovation capacity and increasing local fiscal investment. The findings provide important managerial and policy implications for enhancing regional economic stability and optimizing rural development strategies in the digital era, suggesting that strengthening inclusive digital infrastructure and establishing coordinated fiscal and digital mechanisms are essential for systematically building counties’ capacity for risk resistance and recovery.